Respuesta :

msm555

Answer:

[tex]y = -\dfrac{5}{6}x - 8[/tex]

Step-by-step explanation:

To find the equation of a line passing through the points [tex](0, -8)[/tex] and [tex](-6, -3)[/tex], we can use the point-slope form of a linear equation, which is:

[tex] y - y_1 = m(x - x_1) [/tex]

where [tex](x_1, y_1)[/tex] are the coordinates of a point on the line, and [tex]m[/tex] is the slope of the line.

First, let's find the slope ([tex]m[/tex]) using the given points:

[tex] m = \dfrac{y_2 - y_1}{x_2 - x_1} [/tex]

[tex] m = \dfrac{-3 - (-8)}{-6 - 0} [/tex]

[tex] m = \dfrac{-3 + 8}{-6} [/tex]

[tex] m = \dfrac{5}{-6} [/tex]

[tex] m = -\dfrac{5}{6} [/tex]

Now that we have the slope, let's use one of the points (let's use [tex](0, -8)[/tex]) and the slope to write the equation of the line:

[tex] y - (-8) = -\dfrac{5}{6}(x - 0) [/tex]

[tex] y + 8 = -\dfrac{5}{6}x [/tex]

To write the equation in slope-intercept form ([tex]y = mx + b[/tex]), we need to solve for [tex]y[/tex]:

[tex] y = -\dfrac{5}{6}x - 8 [/tex]

So, the equation of the line passing through the points [tex](0, -8)[/tex] and [tex](-6, -3)[/tex] is:

[tex]y = -\dfrac{5}{6}x - 8[/tex]

Answer:

y = -5/6x - 8

Step-by-step explanation:

We use the point-slope form y - y1 = m(x - x1).

First, we find the slope with the two points (0,-8) and (-6,-3).

We see the y increase by 5 and the x decrease by 6, so the slope is

m = -5/6

Now, we subtitute the number in.

y - (-8) = -5/6(x - 0)

y + 8 = -5/6x

y = -5/6x - 8

ACCESS MORE